Age-related attenuation of cortical synaptic tagging in the ACC is rescued by BDNF or a TrkB receptor agonist in both sex of mice - Si-Bo Zhou; Man Xue; Weiqi Liu; Yu-Xin Chen; Qi-Yu Chen; Jing-Shan Lu; Jinjun Wang; Keqiang Ye; Xu-Hui Li; Min Zhuo (Molecular Brain, 2023)
Abstract Long-term potentiation (LTP) is a key cellular mechanism for learning and memory, and recent studies in the hippocampus found that LTP was impaired in aged animals. Previous studies of cortical LTP have focused primarily on the homosynaptic plasticity in adult mice, while fewer studies have looked at heterosynaptic plasticity—such as synaptic tagging in aged mice. In the present study, we investigated synaptic tagging in adult and middle-aged mice's anterior cingulate cortex (ACC) using the 64-channel multielectrode dish (MED64) recording system. We found that synaptic tagging was impaired in the ACC of middle-aged male mice as compared to adult mice. Both the network late-phase LTP (L-LTP) and the recruitment of inactive responses were reduced in the ACC of middle-aged male mice. Similar results were found in female middle-aged mice, indicating that there is no gender difference. Furthermore, bath application of brain-derived neurotrophic factor (BDNF) or systemic treatment with newly developed TrkB receptor agonists R13, was shown to rescue both synaptic tagging, and L-LTP, in middle-aged mice. To determine the distribution of synaptic LTP within the ACC, a new visualization method was developed to map the Spatio-temporal variation of LTP in the ACC. Our results provide strong evidence that cortical potentiation and synaptic tagging show an age-dependent reduction, and point to the TrkB receptor as a potential drug target for the treatment of memory decline.